IS VITAMIN D ASSOCIATED TO FUNCTIONAL OUTCOMES IN OLDER ADULTS ADMITTED TO REHABILITATION UNITS? - Lelli, D (Innov Aging, 2018)
Vitamin D deficiency is highly prevalent in older people, and it is associated with poor muscular strength and physical performance. Its impact on functional outcomes during geriatric rehabilitation has been poorly studied. We aimed to analyse the association between vitamin D and functional recovery in geriatric rehabilitation units. We conducted a prospective multi-centre cohort study including patients≥65 years old admitted to 3 geriatric rehabilitation units from Italy and Spain, after orthopedic events or stroke. Outcomes were absolute functional gain (AFG, discharge-admission Bathel index) and ability to walk (AW) at 3 months after admission. The association between vitamin D quartiles (Q1-Q2-Q3-Q4) and the outcomes was explored using linear or logistic regression models. We included 420 patients (mean age=81.2 years [SD=7.7], 66.4% females, mean vitamin D concentration=13.5 ng/ml[SD=8.7]). A non-linear relationship between vitamin D and AFG was found, with a stronger association for vitamin D levels<16 ng/ml. Compared to Q1 (vitamin D ≤6 ng/ml), participants in Q3 (vitamin D 11.5–18.2 ng/ml) had the best AFG and AW (Mean AFG[SD]: Q1=28.9[27.8], Q2=32.5[23.5], Q3=43.1[21.9], Q4=34.5[29.3]; AW: Q1-Q2=80%, Q3=91%, Q4=86%). Regression models adjusted for potential confounders confirmed these results (AGF: Q2: β=2.614, p=0.491; Q3: β=9.723, p=0.006; Q4 β=4.406, p=0.222; AW: Q2: OR[95%CI]=1.84[0.67–5.33]; Q3: OR[95%CI]=4.01[1.35–13.48]; Q4: OR[95%CI]=2.18[0.81–6.21]). In conclusion, in our study vitamin D concentration showed a positive association with functional outcomes at 3 months. Interestingly, the best associated levels’ range was below the usual cut-off for “insufficiency”. If confirmed, an early dosage of vitamin D blood concentration may be advisable in geriatric rehabilitation patients.